Comparative Studies of Energy Homeostasis in Vertebrates - Maximilian Michel (Frontiers Research Topics, 2018)
A brief glimpse into new insight driving the comparative biology of energy homeostasis in vertebrates with a focus on non-mammalian vertebrates. What are the key conserved mechanisms and what aspects of feeding behavior and energy allocation are different between species?